Pengaruh Kecerdasan Emosional Dan Kemampuan Beradaptasi Terhadap Kinerja Karyawan CV. Perdana Distribusi Kuala Kapuas - Yona Yolanda; Purboyo Purboyo; Fanlia Adiprimadana Sanjaya (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to examine: (1) Whether Emotional Intelligence affects Employee Performance at CV. Perdana Distribusi Kuala Kapuas, (2) Whether Adaptability affects Employee Performance at CV. Perdana Distribusi Kuala Kapuas, and (3) Whether the Regression Model of Emotional Intelligence and Adaptability is suitable for Employee Performance at CV. Perdana Distribusi Kuala Kapuas. The research design is quantitative and a survey research type. The population of this study consists of all employees of CV. Perdana Distribusi Kuala Kapuas, with a sample size of 37 respondents, and the data analysis used is Multiple Linear Regression.The results of the study indicate: (1) Emotional Intelligence significantly affects Employee Performance at CV. Perdana Distribusi Kuala Kapuas, (2) Adaptability significantly affects Employee Performance at CV. Perdana Distribusi Kuala Kapuas, and (3) Emotional Intelligence and Adaptability simultaneously have a significant effect on Employee Performance at CV. Perdana Distribusi Kuala Kapuas, making the regression model suitable for use. The combination of emotional management skills and flexibility in dealing with change significantly contributes to overall employee performance.